2015
DOI: 10.1016/j.ijscr.2015.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Mammary analog secretory carcinoma of the parotid gland: A case report and literature review.

Abstract: HighlightsMammary analog secretory carcinoma (MASC) is a newly described carcinoma of the salivary glands.MASC is characterized by morphologic and immunohistochemical features that strongly resemble a secretory carcinoma (SC) of the breast.MASC and SC of the breast share the presence of translocation t(12;15) (p13;q25), that results in the formation of an oncogenic fusion gene ETV6-NTK3.The majority of MASC present among men and arise from the parotid gland.MASC is a low-grade carcinoma with potential for high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…1,15 Most of the reported cases showed the behavior of a low-grade adenocarcinoma, with about 15% recurrence rate and 15% rate of lymph node metastases. 16 …”
Section: Discussionmentioning
confidence: 99%
“…1,15 Most of the reported cases showed the behavior of a low-grade adenocarcinoma, with about 15% recurrence rate and 15% rate of lymph node metastases. 16 …”
Section: Discussionmentioning
confidence: 99%
“…From then on, revisiting the medical literature, retrospective studies, and case reports were integrated to scout the incidence of MASC SG . This systematic review surveys almost all the reported cases, after omitting the repeated cases, in order to define our nosology about MASC SG . In 2013, Sethi et al concluded that MASC SG was claimed to be encountered in men more than in women.…”
Section: Introductionmentioning
confidence: 99%
“…Además, el CCA afecta principalmente a las mujeres a diferencia del CSAM, que además es una neoplasia más agresiva si se la compara con el bajo crecimiento regular del CCA 7 . El fenotipo inmunohistoquímico es típicamente S100 y mamaglobina positivo y DOG1 negativo en el CSAM.…”
Section: Discussionunclassified
“…Este tumor afecta predominantemente a los hombres y por lo general no presenta un comportamiento agresivo. Se lo considera como un carcinoma de bajo grado de malignidad; sin embargo, tiene una potencialidad de transformación hacia una lesión de alto grado 7 . En este estudio presentamos un caso de carcinoma secretorio análogo mamario de glándula parótida izquierda diagnosticado por su morfología y con el soporte de la inmunohistoquímica.…”
Section: Introductionunclassified